HOSPITALITY INDUSTRY DURING COVID-19 CRISIS: REVIEW OF THE CURRENT SITUATION AND SUSTAINABLE POST-CRISIS RESPONSE - Ņikadimovs, Oļegs; Rodčenkova, Aļina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This study, titled “Hospitality Industry During COVID-19 Crisis: Review of the Current Situation and Sustainable Post-Crisis Response”, is a review of published studies, assessing the current research efforts in the hospitality industry that was heavily impacted by the COVID-19 global pandemic, as well as possible sustainable crisis management solutions. In response to the crisis, caused by virus outbreak and followed by the travel bans, many hotels were forced to close their doors temporarily or even forever. Such a deep crisis in the hospitality industry resulted in many problems, especially social problems among the employees of the industry. The study has utilised secondary research methodology to conduct a literature review; qualitative content analysis has been applied to the selected academic pieces of literature, journal articles, published researches and thesis papers, government reports, case studies, UNWTO monthly reports. The results revealed approaches and the most popular research directions, as well as possible crisis management solutions and strategies. The findings are highlighting the challenges in tourisms and hospitality industry in the wake of ongoing pandemic; the study lists possible post-crisis sustainable strategic solutions, as well as directions for the future research efforts.